PENERAPAN GOOD CORPORATE GOVERNANCE; DAMPAKNYA TERHADAP PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA - Lingga, Novita (Business Accounting Review, 2013)
This study aimed to know whether the good corporate governance was able to predict the possibility of a company experiencing financial distress. This study used financial ratios as the control variables which were ROA, NPM, and CR. GCG proxied by the Board of Commissioners, the Audit Committee, and Ownership Structure. The samples used in this study were firms of basic and chemical industry sectors with specific criteria. The hypothesis in this study was tested using binary logistic regression analysis with three models to predict which were the model of 1 year, 2 years, and 3 years before financial distress or non-financial distress status. The results proved that in all three models, the partial GCG score consistently was able to predict the probability of a firm experiencing financial distress. Meanwhile, ROA and NPM in all three models were not able to predict the probability of a firm experiencing financial distress, and CR only in model 1 was able to predict the possibility of a company experiencing financial distress. The results also proved that model 1 produce the best of conformance test and the greatest prediction accuracy.